Dietary Soluble Fiber Improved Fecal Consistency in Burned Patients with Diarrhea - Setiawan, Evania; Wardhana, Aditya; Sinaga, Wina; Sari, Ayu Diandra; Satyani, Metta; Octovia, Lily Indriani (Lingkar Studi Bedah Plastik Foundation, 2021)
Backgrounds: Diarrhea frequently occurs in severely burned patients attributable to impaired intestinal integrity and dysbiosis. Soluble fiber may improve intestinal barrier function, avoid bacterial translocation, then subsequently prevent and treat diarrhea. Soluble fiber is rapidly fermented by commensal bacteria and produces short-chain fatty acids (SCFA). Case Reports: A 51-year-old male with severe burn injury involving 53,5% total body surface area (TBSA) and diarrhea were given soluble fiber as part of his diet. Results: Administration of 6–10 g/d soluble fiber clinically improves stool consistency, assessed by Bristol Stool Scale, in the severely burned patient. The patient was discharged after 19 days of hospitalization with improvement in clinical condition. Summary: SCFA maintains intestinal integrity, supports the growth of commensal bacteria, and inhibits pathogens. There is no specific recommendation regarding fiber intake in burned patients